Hot, flat, and crowded why the world needs a green revolution - and how we can renew our global future - Friedman, Thomas (London Penguin, 2009)
Thomas L. Friedman's phenomenal number-one bestseller The World is Flat has helped millions of readers see the world in a new way. In this essential new book, Friedman takes a fresh and provocative look at two of the biggest challenges we face today: the global environmental crisis and America's surprising loss of focus and national purpose since 9/11. It is a groundbreaking account of where we stand now, and he shows us how the solutions to these two big problems are linked - how we can restore the world and revive America at the same time.
Includes index.
Keywords: Climatic changes; Population -- Environmental aspects; Green movement; Green technology